Wood formaldehyde analysis – affecting factors, evaluation methodologies and minimisation solutions / Yung Yen Li - Yung, Yen Li (2013)
Although formaldehyde has been declared as a ‘human carcinogen’, world demand for this organic compound is remained strong as there is no suitable substitute for its multi applications. A study was carried out to determine the effects of wood species and its moisture content on the formaldehyde emission. In the quantitative analysis, solid phase micro-extraction sampling from the absorbing solution (SPME-A) and air sampling directly from the wood specimen (SPME-W) were used for comparison with the existing methods: desiccator-acetyl acetone (DC-AA), small chamber chromotropic acid (SC-CA) and liquidliquid extraction with different detectors (LLE-FID and LLE-ECD). Meanwhile, the plywood was treated to upgrade its formaldehyde classes physically by increasing the surface veneer thickness and through chemical scavenging. Both moisture content and wood species significantly affected the formaldehyde emission. Validation of the SPME method was evidenced. It showed better repeatability (RSD 1.8 %) and proven to be highly precise (at the 95% confidence level) with better efficacy by exhibiting a good level of recovery (102%). In addition, the SPME method exhibited better linearity with regression value of 0.9982. Furthermore, the limit of detection (0.01 mg/L) and limit of quantification (0.02 mg/L) obtained enlarged the coverage of the SPME for trace levels of formaldehyde determination. The SPME-W method best correlated with DC-AA (R2 = 0.9834) for original samples and with the LLEECD(R2 = 0.9486) for treated samples. The headspace SPME proved to be a reliable alternative in the volatile formaldehyde determination similar to the other official methods used. Both the physical and chemical treatments were found to be effective in formaldehyde minimisation and to reach the permitted safe level of emission.